Exploring the mediating roles of self-confidence and mathematical resilience in the relationship between problem-based learning and students’ mathematical literacy - Muhammad Sukri Situmeang; Ahmad Dimyati; Chasan Ma’ruf (CV. FOUNDAE, 2026)
Background: Mathematical literacy is widely recognized as a key competence that enables students to interpret, analyze, and apply mathematical ideas in everyday contexts. Despite its importance, many students still experience difficulties developing this competence due to limited opportunities for meaningful problem solving and insufficient support for affective factors such as confidence and resilience. Aims: This study aimed to investigate the mediating roles of self-confidence and mathematical resilience in the relationship between Problem-Based Learning (PBL) and students’ mathematical literacy. Method: A true experimental design with a posttest-only control group was employed. The participants consisted of students from four State Islamic Junior High Schools in Bogor Regency selected through multistage random sampling. The experimental group was taught using the PBL approach, while the control group received conventional instruction. Data were collected using a mathematical literacy test and questionnaires measuring students’ self-confidence and mathematical resilience. The data were analyzed using independent samples t-tests, path analysis, and Sobel tests to examine both direct and indirect relationships among variables. Results: The findings revealed that students exposed to PBL achieved significantly higher scores in mathematical literacy, self-confidence, and mathematical resilience than those in conventional classes (p < 0.05). Path analysis indicated that PBL had a direct positive effect on mathematical literacy, while both self-confidence and mathematical resilience acted as significant mediators. Conclusion: These findings suggest that PBL can enhance students’ mathematical literacy not only through instructional processes but also by strengthening important affective attributes in mathematics learning.